Dampak nyata pengabdian perguruan tinggi dalam membangun negeri - Almasdi Syahza (Unri Conference Series: Community Engagement, 2019)
Human resources produced by universities must be involved in increasing the nation's competitiveness. Science and technology and higher education can contribute to strengthening the economy and improving people's welfare. It is shown by the technology advantage produced and partnerships with the industrial sector. Higher education institutions in Indonesia have produced innovations that bring direct benefits to the community. Community service activities are a form of university involvement in implementing knowledge. Higher education must convince academics to think that the Tri Dharma of higher education is a package of activities and a symbol of the success of an institution as a college. Community service can empower people by applying appropriate technology, problem-solving models, and social design. Community services of higher education can produce intellectual property rights and also policy recommendations that can be applied by the community, business, industry, and government.